Visualizing The Knowledge Structure of Geriatric Rehabilitation: A Bibliometric Analysis - Azizan, Azliyana; Rahayu, Sri Ratna (Jurnal Kesehatan Masyarakat, 2024)
This study undertakes a comprehensive bibliometric analysis to visualize the knowledge landscape of geriatric rehabilitation. Utilizing the Web of Science and Scopus databases from 1947 to 2023, a meticulous bibliometric analysis was executed. The research was facilitated through ScientoPy and VOSviewer tools, enabling meticulous scrutiny and insightful visualization of the research network. A total of 5120 papers were identified through the search strategy. The outcomes reveal the United States as the foremost contributor to geriatric rehabilitation research, with the Archives of Physical Medicine and Rehabilitation emerging as a highly active journal. Among the most significant author’s keywords, “rehabilitation”, “aged” and “hip fracture” are prominent, underscoring pivotal domains for targeted interventions within geriatric care. Furthermore, this analysis highlights noteworthy keywords such as “sarcopenia,” “physical activity,” and “virtual reality,” offering essential insights into core themes within geriatric rehabilitation. Consequently, this study presents a valuable resource for scholars and researchers alike. It serves as a foundational tool for identifying prevalent research trends, addressing existing gaps, and embarking on new explorations in the dynamic realm of geriatric rehabilitation. The findings provide a holistic understanding of the knowledge landscape, paving the way for informed decision-making, innovative research endeavors, and the enhancement of geriatric rehabilitation practices.